High bifurcation of the median nerve at carpal tunnel syndrome: case study - Goloborod’ko, Sergey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
High bifurcation of the median nerve is a relatively rare pathology in carpal tunnel syndrome, a description of which is rarest. The transposition of the median nerve in the case of this abnormality is not reported at all. Objective: to acquaint readers with a relatively rare case of the anatomical structure of the median nerve, which was discovered during the surgical treatment of the carpal tunnel syndrome. Methods: a 54 years old woman M. complained of constant numbness and intense night pain in the I–IV fingers of the left hand. According to the patient, these clinical manifestations appeared without any reason 9 months ago. The patient has got conservative treatment without positive effect. After a clinical examination a preliminary diagnosis was made: idiopathic carpal tunnel syndrome of the left hand. Surgical treatment was performed: the transposition of the median nerve. Results: after a Z-shaped dissection of the flexor retinaculum, a median nerve was detected, which was divided into two separate branches, while the ulnar branch was thinner than the radial one. Nerve bifurcation continued both distal and proximal to the edges of the skin wound. No additional abnormalities were found. In the follow-up 2 years after the surgery, numbness and finger pain were absent, thenar atrophy disappeared, the opposition of the thumb was restored. Conclusions: a case of high bifurcation of the median nerve is described in order to remind physicians that such abnormality, although infrequently, can occur both in the surgical treatment of injuries of the median nerve and carpal tunnel syndrome. Moreover, during the surgery for carpal tunnel syndrome, it is important to know that the branches of the bifurcated median nerve can be compressed in separate tunnels, and therefore it is necessary to perform decompression and revision of the nerve in both tunnels, which can be quite difficult with the endoscopic method of surgical treatment.